Relationship between carotid atherosclerosis and coronary artery calcification in asymptomatic diabetic patients: A prospective multicenter study. Issue 9 (25th May 2017) - Jeevarethinam, Anand; Venuraju, Shreenidhi; Dumo, Alain; Ruano, Sherezade; Mehta, Vishal S.; Rosenthal, Miranda; Nair, Devaki; Cohen, Mark; Darko, Daniel; Lahiri, Avijit; Rakhit, Roby
Abstract : Background: The value of screening sub‐clinical atherosclerosis in asymptomatic patients with type 2 diabetes mellitus (T2DM) remains controversial. Hypothesis: An integrated model incorporating carotid intima‐media thickness (CIMT) and carotid plaque with traditional risk factors can be used to predict prevalence and severity of coronary artery calcification in asymptomatic T2DM patients. Methods: A cohort of 262 asymptomatic T2DM patients were prospectively studied with carotid ultrasound to evaluate CIMT and carotid plaque and also a computed tomography coronary artery calcium (CT‐CAC) scan. Results: Carotid plaque was detected in 124 (47%) patients and mean CIMT was 0.75±0.14 mm. Two hundred (76%) patients had a CAC score >0, of whom 57 (22%) had severe coronary atherosclerosis (>400 Au). In this group, carotid plaque was present in 40 (70%) patients (p<0.001). Univariable analysis revealed significant associations between non‐zero CAC score and age (p<0.001), hypertension (p=0.01), gender (p=0.003) and duration of diabetes (p=0.004). Carotid plaque and mean CIMT were also significantly associated with non‐zero CAC score (odds ratios [95% CI], 3.12 [1.66 ‐5.85] and 2.98 [0.24 ‐7.17], respectively). After adjusting for traditional risk factors, carotid plaque continued to be predictive of non‐zero CAC score (2.59 [1.17 ‐5.74]) and CIMT was borderline significant (p=0.05). When analysed with binary logistical regression, the prevalence of carotid plaque significantly predicted severe CAC burden (CAC >400 Au; 3.26 [2.05 ‐5.19]). Upper CIMT quartiles showed a similar association (2.55 [1.33 ‐4.87]). Conclusion: Carotid plaque is more predictive of underlying silent coronary atherosclerosis prevalence, severity and extent in asymptomatic T2DM patients.